2020
DOI: 10.3390/molecules25163753
|View full text |Cite
|
Sign up to set email alerts
|

Inequality in the Frequency of the Open States Occurrence Depends on Single 2H/1H Replacement in DNA

Abstract: In the present study, the effect of 2H/1H isotopic exchange in hydrogen bonds between nitrogenous base pairs on occurrence and open states zones dynamics is investigated. These processes are studied using mathematical modeling, taking into account the number of open states between base pairs. The calculations of the probability of occurrence of open states in different parts of the gene were done depending on the localization of the deuterium atom. The mathematical modeling study demonstrated significant inequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 62 publications
(93 reference statements)
1
14
0
Order By: Relevance
“…Perhaps, in our opinion, the key mechanism is the chirality of substances in methylene groups with deuterium or protium in their structure. Recent data with a single 2 H/ 1 H replacement in DNA confirm this mechanism [65]. Therefore, further experimental data will help to solve the mechanism of action of deuterated or deuterium-depleted aqueous media on living organisms.…”
Section: Kinetic Model Of the Vital Activity Of Living Organisms Depending On The D/h Ratiomentioning
confidence: 84%
“…Perhaps, in our opinion, the key mechanism is the chirality of substances in methylene groups with deuterium or protium in their structure. Recent data with a single 2 H/ 1 H replacement in DNA confirm this mechanism [65]. Therefore, further experimental data will help to solve the mechanism of action of deuterated or deuterium-depleted aqueous media on living organisms.…”
Section: Kinetic Model Of the Vital Activity Of Living Organisms Depending On The D/h Ratiomentioning
confidence: 84%
“…In our previous study for N·m energy range [ 29 ], the inequality in the frequency of the open states occurrence because of the single 2 H/ 1 H replacement in gene encoding interferon alpha 17 (IFNA17, which consists of 980 nucleotide pairs [ 30 ]) was proved through it conditionally divided into three equal parts: from the 1st to the 327th nucleobases (I part), from the 328th to the 653th nucleobases (II part) and from the 654th to the 980th nucleobases (III part). This approach allowed us to contemplate the influence on probabilities ( ) of open state occurrences between different nitrogenous bases in double-stranded DNA dependent on the single 2 H/ 1 H replacement in basepair of each gene region.…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, even relatively small increases or decreases in its concentration affect physiological processes at all levels: molecular, cellular, tissue, organ and organism [ 6 , 7 , 8 , 9 , 10 ]. Many studies have shown that a decrease in the deuterium content supports the body’s defense systems, including nonspecific mechanisms [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%